Auditing tools for antimicrobial prescribing in solid organ transplant recipients: The why, the how, and an assessment of current options. Issue 5 (18th October 2022) - So, Miranda; Nakamachi, Yoshiko; Thursky, Karin
Abstract: Background: Antimicrobial stewardship (AMS) aims to optimize antimicrobial use. Auditing and reporting of antimicrobial prescribing are essential. Auditing tools for solid organ transplant (SOT) patients should tailor to their needs. Methods: We reviewed published data describing auditing tools in the general and SOT population. Results: We focused on three internationally or nationally available auditing tools. The National Antimicrobial Prescribing Survey (NAPS) is web‐based tool to report antimicrobial consumption and assess appropriateness using standardized definitions based on consensus guidelines. In the absence of guidelines, adjudication is based on AMS principles. An automated dashboard, analyses by indication or antimicrobial, and benchmarking reports are available. The National Healthcare Safety Network Antimicrobial Use/Resistance module was developed by the Centers for Disease Control and Prevention for hospitals to upload monthly data, which are standardized for benchmarking. It does not assess appropriateness or address SOT wards. The Global‐Point Prevalence Survey from bioMérieux collects data on antimicrobial regimen, indication and microbial resistance. Variables unique to SOT include comorbidities and devices. Assessment of appropriateness is limited to guideline adherence, and benchmarking may require prearrangement with bioMérieux. Benchmarking requires prearrangement. Advances in electronic health record systems and clinical decision support tools can improve the efficiency of the auditing process. Conclusion: Each AMS auditing tool has unique features for SOT patients. Capturing immunosuppression, source control, organ dysfunction, donor‐derived infection, serology, and colonization status will enhance their applicability.